Learn cocos2d 2 : game development for iOS - Itterheim, Steffen (Apress : Distributed to the Book trade worldwide by Springer Science+Business Media, 2012)
Create compelling 2D games with Learn cocos2d 2: Game Development with iOS . This book shows you how to use the powerful new cocos2d, version 2 game engine to develop games for iPhone and iPad with tilemaps, virtual joypads, Game Center, and more. It teaches you: The process and best practices of mobile game development, including sprite batching, texture atlases, parallax scrolling, touch and accelerometer input. How to enhance your games using the Box2D and Chipmunk physics engines and other cocos2d-related tools and libraries. How to add UIKit views to cocos2d and how to add cocos2d to UIKit apps. The ins and outs of the Kobold2D development environment for cocos2d and its pre-configured libraries, including cocos3d and Lua. Best of all, this book will have you making games right from the very start. It guides you step-by-step through the creation of sample games. These fun examples are modeled after popular App Store games and teach you key concepts of the new cocos2d 2 game engine and relevant tools like TexturePacker (texture atlas), PhysicsEditor (physics collision shapes), Particle Designer (particle effects), Glyph Designer (bitmap fonts), and others. This book offers a rock-solid introduction to creating games made entirely with cocos2d and little or no iOS SDK and OpenGL code. It also details alternative implementations, identifies the best free and commercial tools for cocos2d game development, features coverage of the author's improved cocos2d game engine (Kobold2D), and even helps you enhance your game's marketability on the App Store. What you'll learn The process and best practices of mobile game development, including sprite batching, texture atlases, parallax scrolling, touch and accelerometer input. How to enhance your games using the Box2D and Chipmunk physics engines and other cocos2d-related tools and libraries. How to add UIKit views to cocos2d and how to add cocos2d to UIKit apps. The ins and outs of the Kobold2D development environment for cocos2d and its pre-configured libraries, including cocos3d and Lua. Who this book is for The book is aimed at beginning game developers looking for an easier and even more powerful way to create compelling 2D graphics using OpenGL and Objective-C. It is assumed that the reader will have some knowledge of object-oriented programming and the Apple and iPhone/iPad developer environment.